Retratos da dislexia no Brasil : análise bibliográfica do período de 2002 a 2014 - Oliveira, Patricia de (Universidade Federal de São Carlos, 2016)
The Dyslexia field of study is marked by tensions and controversies about the possible causes of the difficulties of learning the written language made by children during literacy. The dominant thinking has understood dyslexia as a product of neurobiological disorders that affect the processing responsible for reading and writing. In contrast, critical researchers to this hegemony have stated that the acquisition of writing should be understood as a cultural process in which children exercise their subjectivity. Thus, errors made in writing should be understood as an exercise of this subjectivity and experience with this object of culture. Considering these aspects, this study aimed to analyze academic theses and dissertations developed during the period 2002-2014, in order to understand how the concept of dyslexia has been developed and what their implications for education . The assumed methodology was a literature review. Theses and dissertations analyzed were raised in the pages of CAPES and BDTD. The survey pointed to 72 research. To better meet the proposed goal, this research was divided into two studies. In Study 1, which were analyzed all the research raised under the chronological distribution categories, region of the country, administrative category, Community College, Graduate Programs, Search Types, Research Subjects, theoretical approaches and dyslexia conceptions and findings and conclusions of the studies analyzed. The considerations of this study show that the hegemony of scientific thought which defines dyslexia as a neurobiological disorder may be hindering the development of new insights into the phenomenon and also crystallizing the concept of disabling condition, which follows the opposite of proposals for inclusive education. In Study 2, only we analyzed the research developed in the field of study of education in the following categories: type of study and research methodology, dyslexia conceptions of learning, on the acquisition and development of reading, teaching, education, and what are their contributions to school practices. The considerations of this study show the same dominance of present scientific thinking on the analysis by the Study 1, added to an excessive concern with the diagnosis and considerable uncertainty about the way they are the written language learning processes. The Final remarks raised concern over the proposed school model and the way may be implying about individuals.
Keywords: Dislexia; Aprendizagem; Linguagem escrita; Educação especial; Pesquisa bibliográfica; Dyslexia; Learning; Written language; Special education; Bibliographic research; CIENCIAS HUMANAS::EDUCACAO